The role of the Orthodox clergy of the North Caucasus in the incorporation of the region into the Russian Empire in the middle of the XIX century - Kolosova, O. Yu; Nemashkalov, P. G. (Гуманитарные и юридические исследования, 2024)
Introduction. The reference to the history of forming an independent Caucasian and Black Sea diocese is due to the study of the problem of the incorporation of the North Caucasus into the Russian Empire. In the absence of an extensive system of administrative control bodies and a protracted military conflict in the first half of the 19th century, the process of searching for a platform of national identity was underway, which allowed not only to reduce the level of escalation of the conflict, but also to incorporate the North Caucasus into the socio-cultural space of the Russian Empire. Materials and Methods. The study is based on the principles of an interdisciplinary approach, which allowed us to consider the problem in its entirety, combine data obtained from different fields, look at the problem of the influence of the clergy and the Orthodox cultural tradition from different positions, expand and deepen the existing body of scientific knowledge on this issue. The method used made it possible to conduct modern historical research from the standpoint of historical anthropology. In addition, the work uses narrative, historicalgenetic, historicaltypological, retrospective and anthropological research methods. The research is based on materials from archival collections and review articles of the Caucasian (Stavropol) Diocesan Gazette. The analysis of the problems raised is reflected in the works of researchers of the history of the Cossacks V.A. Potto, F.A. Shcherbina, and the nature of colonization of the region G.N. Prozritelev. The organization of church administration and the personality of the first bishop Jeremiah (Solovyov) was analyzed in the study by I.K. Smolich. Results. According to the results of the study, it can be concluded that, being in the minority in relation to the ascetics of Islam, Old Believers, sectarians inhabiting the region, the Orthodox population managed to create the basis for the spiritual unity of the population of the region. The traditions of Orthodox culture in the North Caucasus have become the basis of ethnocultural identity, acting as a historical and cultural landmark for a certain part of the population.